Intra‐observer reliability for measuring first and second toe and metatarsal protrusion distance using palpation‐based tests: a test‐retest study - Carmen‐Belén Martínez‐Cepa; Juan‐Carlos Zuil‐Escobar; Raquel Chillón‐Martínez; José‐Jesús Jiménez‐Rejano; Inmaculada‐Concepción Palomo‐Toucedo (Journal of Foot and Ankle Research, 2014)
Abstract Background Measurement of first and second metatarsal and toe protrusion is frequently used to explain foot problems using x‐rays, osteological measurements or palpation‐based tests. Length differences could be related to the appearance of problems in the foot. A test‐retest design was conducted in order to establish the intra‐rater reliability of three palpation‐based tests. Methods 202 feet of physical therapy students and teachers of the CEU San Pablo University of Madrid, 39 men and 62 women, were measured using three different tests. Data were analysed using SPSS version 15.0. Mean, SD and 95% CI were calculated for each variable. A normal distribution of quantitative data was assessed using the Kolmogorov‐Smirnov test. The test‐retest intra‐rater reliability was assessed using an Intraclass Correlation Coefficient (ICC). The Standard Error Mean (SEM) and the Minimal Detectable Change (MDC) were also obtained. Results All the ICC values showed a high degree of reliability (Test 1 = 0.97, Test 2 = 0.86 and Test 3 = 0.88) as did the SEM (Test 1 = 0.07, Test 2 = 0.10 and Test 3 = 0.11) and the MDC (Test 1 = 0.21, Test 2 = 0.30 and Test 3 = 0.31). Conclusions Reliability of measuring first and second metatarsal and toe protrusion using the three palpation‐based tests showed a high degree of reliability.